A 14-year-old girl presenting with tuberculous intestinal perforation while in a temporary shelter after the 2015 earthquake in Nepal. (2nd January 2018) - Shrestha, Dhruba; Shrestha, Manoj Krishna; Raya, Ganendra Bhakta; Bhattachan, Anuj; Hayashi, Kentaro; Ariyoshi, Koya; Parry, Christopher M.; Dhoubhadel, Bhim Gopal
Abstract: A 14-year-old Nepalese girl presented with fever, abdominal pain and vomiting. She was living with her family in a temporary settlement camp following the earthquake in Nepal in 2015. She had had abdominal pain for 2 months and fever for 1 month. Abdominal examination suggested acute peritonitis. At laparotomy, three ileal perforations were detected and histopathology demonstrated caseous granulomas. Her father had sputum-positive pulmonary tuberculosis. She was diagnosed with abdominal tuberculosis and responded well to anti-tuberculosis chemotherapy. Intestinal perforation is a rare complication of tuberculosis in children.